Generalized Free Products of Residually $P$-Finite Groups - Wong, P.C.; Tang, C.K.; Gan, H.W. (2006)
In this note, we characterize the residual p-finiteness of generalized free products and tree products of certain residually p-finite groups with non-trivial center amalgamating infinite cyclic subgroups and the tree products of certain one-relator groups. We then apply our results to tree products of finitely generated torsion-free nilpotent groups and free groups.